Continuity planning for public health crises: Designing workplace redundancies for organizational resilience - Grace, Rob; Gautam, Sanjana; Tapia, Andrea (Journal of emergency management (Weston, Mass.), 2023)
Continuity planning prepares organizations to maintain essential functions despite disruptions to critical infrastructure that occur during crises. Continuity planning is especially important for Public-Safety Answering Points (PSAPs), which must prepare to answer 911 calls and dispatch first responders in all-hazard environments, including public health crises such as the COVID-19 pandemic. However, continuity planning typically focuses on disruptions to cyber-physical infrastructure rather than social infrastructure disruptions that occur when outbreaks of communicable disease limit the ability of essential personnel to perform an organization's essential functions. Reporting findings from interviews with US officials, this study examines how PSAPs decentralized essential personnel by designing redundant workplaces during the COVID-19 pandemic. Realizing existing continuity plans prepared PSAPs to relocate and recentralize essential personnel in a single, shared workplace, officials developed new plans to protect and decentralize telecommunicators across multiple, separate workplaces. To do so, PSAPs achieved passive, standby, and active workplace redundancies that recommend continuity planning objectives and requirements for organizations preparing for future public health crises.